2013
DOI: 10.1186/1752-153x-7-64
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antifungal activities of novel nicotinamide derivatives containing 1,3,4-oxadiazole

Abstract: BackgroundPant diseases in agriculture are extremely difficult to control, which bring about for billions of dollars in economic losses worldwide each year; Nicotinamide derivatives has attracted more and more attention in the field of pesticide due to their broad bioactivities. In an effort to discover new molecules with good antifungal activity, a series of nicotinamide derivatives containing 1,3,4-oxadiazole were synthesized and bio-assayed.ResultsBioassays demonstrated that some of the title compounds exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…[10][11][12][13][14][15][16] Such as sulfoxaor, a representative commercial insecticide, and was industrialized by Dow Agroscience. 16 1,3,4-Oxadiazole derivative is a highly active pharmacophore and widely was used in pesticide molecules, 17 many active substance containing such a scaffold have been reported as insecticides, [18][19][20][21][22][23][24] fungicides, [25][26][27][28][29][30][31] and herbicides, 32-34 some of them were treated as a pesticide candidate for further industrialization. 25 Recently, Liu and co-workers reported the 1,3,4-oxadiazole derivative with an anthranilic diamide moiety possessed excellent insecticidal activity against P. xylostella, 20 as well as some insecticidal sarisan analogues with an 1,3,4-oxadiazole scaffold were developed by Guo et al 23,35 And in our recent work, a series of insecticidal 1,3,4-oxadiazole molecules bearing a 3-chloropyridin-2-yl-1H-pyrazole was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Such as sulfoxaor, a representative commercial insecticide, and was industrialized by Dow Agroscience. 16 1,3,4-Oxadiazole derivative is a highly active pharmacophore and widely was used in pesticide molecules, 17 many active substance containing such a scaffold have been reported as insecticides, [18][19][20][21][22][23][24] fungicides, [25][26][27][28][29][30][31] and herbicides, 32-34 some of them were treated as a pesticide candidate for further industrialization. 25 Recently, Liu and co-workers reported the 1,3,4-oxadiazole derivative with an anthranilic diamide moiety possessed excellent insecticidal activity against P. xylostella, 20 as well as some insecticidal sarisan analogues with an 1,3,4-oxadiazole scaffold were developed by Guo et al 23,35 And in our recent work, a series of insecticidal 1,3,4-oxadiazole molecules bearing a 3-chloropyridin-2-yl-1H-pyrazole was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The key building blocks ortho-amino aryl acid 1 and 2 were selected as starting materials, and which could be conveniently transferred to the corresponding oxazinone heterocyclic intermediates 3 via a classical heterocyclization reaction [ 13 , 20 , 23 25 ] with simple procedures. Then these oxazinones were treated with various amines resulting in the target nicotinamide-based diamides derivatives 4a–k via nucleophilic substitution reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many nicotinamide derivatives have been reported for their broad pharmacological properties such as anticancer [ 9 11 ], anti-angiogenic [ 9 ], and antinociceptive effect [ 12 ] etc. Meanwhile, some nicotinamide derivatives have also been developed as agrochemicals for their insecticidal, herbicidal, and fungicidal activities [ 13 18 ]. In addition, many diamides derivatives have been investigated for their wide range of pharmacological activities including antitumor [ 19 , 20 ], anti-inflammatory activities, Factor Xa inhibitors [ 21 ], CCK1 receptor antagonists [ 22 ], and insecticidal and fungicidal activities [ 23 25 ] etc., and which all demonstrated this diamide scaffold might be an important pharmacophore for drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…The bioassay results have shown that some of them exhibited excellent antifungal activities. [23][24][25][26][27][28] It has been proven that pyridine carboxamide group display fungicidal activity by disrupting the mitochondrial tricarboxylic acid cycle (TCA) through inhibition of the succinate dehydrogenase (SDH) enzyme, also called succinate ubiquinone oxidoreductase (SQR). [29] The most of fungicides are heterocyclic toxic substances which selectively destroy fungal phytopatho-gens ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%